#TITLE_ALTERNATIVE# - DIAH AYU KUSUMAWARDANI, SYLVIA
Air pollution can also occur in indoor. Indoor air pollution can be affected by human activities or penetration of ambient air pollution that occured outdoor, such as transportation, industry, waste burning, and another ambient air pollution sources. This research will investigated the influence of outdoor PM10 concentration, especially that emitted from transportation sector, and indoor PM10 concentration in ten houses located on the roadside. Samples were taken at the terrace that represent the ambient air potentially penetrating into indoor air, and at the front living room that represent the quality of indoor air influenced by outdoor. PM10 concentration data were obtained by Low Volume Sampler (LVS) and then were analyzed gravimetrically in the laboratory. Concentration found from will be compared to get the ratio of indoor concentration to outdoor concentration (I/O). The relationship between these two variables was investigated by analysis of variance, namely independent sample t-test. From this analysis, it is found that there was no significant difference between indoor PM10 concentration and outdoor PM10 concentration (t = 1.417 and p = 0.174), indicating that outdoor has a significant effect on indoor PM10 concentration. The average ratio of I/O was found to be by 1.4617. This result indicates that indoor air pollution is greater than outdoor and suggests that beside the possibility of intrusion of contaminants from outside to inside the house, some indoor also PM10 sources are also existed.